Hubungan antara Media Aplikasi Google Classroom dan Kreativitas Siswa dengan Prestasi Belajar Pendidikan Agama Islam Siswa di Bekasi. - Ahmad Marzuki; Moh Fahri Yasin (Al-Ulum, 2022)
The purpose of this study was to determine the relationship between there is a significant relationship between the google classroom application media and PAI learning achievement, a significant relationship between student creativity, and a significant relationship between the google classroom application media and student creativity together with PAI learning achievements of students in Bekasi. The research method used in this study is survey and correlation methods. In this study the instrument used was a questionnaire primary data and learning outcomes using secondary data.The results of this study are the first, the google classroom application media has a significant relationship with PAI learning achievement. Evidenced by the results of data analysis (t count 5.165 > t table 1.67).KSecond, student creativity has a significant relationship with Islamic education learning achievement. Third, the google classroom application media and student creativity together have a significant relationship with PAI learning achievement.